THE RIGHT TO ENVIRONMENT IN TURKISH LAW AND JURISPRUDENCE - (:unkn) unknown (G V ZALOZBA PUBLISHING HOUSE LTD, 2012)
This article provides an analysis of Turkish law and Turkish Supreme Court decisions to explain what the extent of the right to environment is in Turkish law and practice. The article concludes that although a substantive right to environment is well established in Turkish law, it is not adequately accompanied by procedural rights. The purpose of the final part of the article is to evaluate Turkish law and jurisprudence in relation to the international environmental law instruments. The article concludes that Turkey's unwillingness to become a party to Aarhus Convention is an important deficiency with regard to environmental protection and that Turkish courts are reluctant to address international law instruments in environmental matters. However rare references to the contrary can also be found.
Keywords: right to environment; international environmental law instruments; Turkish law; Turkish Supreme Court decisions